Penggunaan Teknik Blok Perifer Angkle pada Pasien Papo Digiti 4,5 Pedis Sinistra - Mahmud; Triputra, Audhiaz Marthsyal; Artika, I Gusti Ngurah Rai (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2018)
A 75 yearl old woman diagnosed gangrenous 4th – 5th left digiti pedis e.c susp. PAPO went to surgery with amputation of the 4th and 5th left digiti pedis with a peripheral nerve block anesthesia techniques. Preoperative physical status been classified with ASA II, with warfarin therapy has been discontinued since 4 days ago and replaced with UF heparin for one day therapy. The operation takes approximately less than one hour with hemodynamically stable, patients had no complaints of pain to post-surgery. Heparin therapy then continued one day after surgery